2006
DOI: 10.1055/s-2006-948207
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Bromination of Active Methylene and Methyne Compounds by Potassium Bromide, Hydrochloric Acid and Hydrogen Peroxide

Abstract: Active methylene and methyne compounds can be chemoselectively brominated in high yields using potassium bromide, hydrochloric acid, and hydrogen peroxide at room temperature.Halogenated active methylene and methyne compounds are very important synthetic intermediates for the nucleophilic substitutions in synthetic organic chemistry. The classical methods of halogenation of active methylene and methyne compounds 1 are the reaction with bromine 1 or sulfuryl chloride, 2 however, they suffer from drawbacks such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…[10] A combination of KBr, HCl (5 equiv of each), and an excess of H 2 O 2 have been applied to the chemoselective bromination of the active methylene group of 1,3-dicarbonyl compounds in toluene at room temperature (Scheme 23). [101] Interestingly, it was observed that the use of a mechanical stirrer instead of a magnetic one was more effective in driving the reaction, and that only 1 equivalent of KBr and HCl and 1.2 equivalents of H 2 O 2 were sufficient to obtain quantitative yields of brominated products.…”
Section: Oxidative Halogenationmentioning
confidence: 99%
“…[10] A combination of KBr, HCl (5 equiv of each), and an excess of H 2 O 2 have been applied to the chemoselective bromination of the active methylene group of 1,3-dicarbonyl compounds in toluene at room temperature (Scheme 23). [101] Interestingly, it was observed that the use of a mechanical stirrer instead of a magnetic one was more effective in driving the reaction, and that only 1 equivalent of KBr and HCl and 1.2 equivalents of H 2 O 2 were sufficient to obtain quantitative yields of brominated products.…”
Section: Oxidative Halogenationmentioning
confidence: 99%
“…A plausible reaction mechanism is that bromide ion is oxidized by hydrogen peroxide into the bromo ion (Br þ ) which reacts with the enol form of the active methylene compound providing selectively the desired monobromo derivative while only nontoxic potassium chloride and water are produced as a waste [30].…”
Section: Chemistrymentioning
confidence: 99%
“…The freshly prepared solution of DHIQCDS (18) (25 mg/mL in DMSO) was injected through the external jugular vein at a dose of 20 mg/kg of body weight. At appropriate time intervals (5,15,30,45, 60, 75 min) blood samples were withdrawn from the eyeball and added immediately to a previously weighted centrifuge tubes containing 4 mL of acetonitrile, then reweighed to determine the amount of the blood added. The animal was then decapitated, and the brain was removed quickly, washed with ice cold saline solution, weighed, wrapped in aluminum foil and immediately kept in the freezer together with the blood samples.…”
Section: In Vivo Distribution Studymentioning
confidence: 99%
“…Masayuki et al reported chemoselective bromination of active methylene and methine compounds using potassium bromide, hydrochloric acid and hydrogen peroxide [47]. Recently, we have reported the facile synthesis of β-keto-sulfones [48] and direct synthesis of α-iodo β-keto-sulfones and their base-induced cleavage to afford α-iodomethyl sulfones [49].…”
Section: Introductionmentioning
confidence: 98%